Mom, Dad it’s only a game! Perceived gambling and gaming behaviors among adolescents and young adults: an exploratory study - Calado, C. (2014)
Gambling and gaming are increasingly popular activities among adolescents. Although gambling is illegal in Portugal for youth under the age of 18 years, gambling opportunities are growing, mainly due to similarity between gambling and other technology-based games. Given the relationship between gambling and gaming, the paucity of research on gambling and gaming behaviors in Portugal, and the potential negative consequences these activities may have in the lives of young people, the goal of this study was to explore and compare the perceptions of these two behaviors between Portuguese adolescents and young adults. Results from six focus groups (comprising 37 participants aged between 13 and 26 years) indicated different perceptions for the two age groups. For adolescents, gaming was associated with addiction whereas for young adults it was perceived as a tool for increasing personal and social skills. With regard to gambling, adolescents associated it with luck and financial rewards, whereas young adults perceived it as an activity with more risks than benefits. These results suggest developmental differences that have implications for intervention programs and future research.